An efficient protocol for the synthesis of thioethers via iron-catalyzed cross-coupling reaction and its mechanistic investigation. (15th January 2019) - Sindhu, K.S.; Abi, T.G.; Mathai, George; Anilkumar, Gopinathan
Graphical abstract: Experimental and mechanistic exploration of Fe‐catalyzed thioetherification of aryl halides with aryl thiols using non-toxic and universal ligandl -proline. Abstract: One of the most straightforward methods for the synthesis of diaryl sulfides is the transition metal catalyzed CS coupling reaction. Herein we report a study on the iron-catalyzed protocol for cross-coupling reaction of aryl halides with thiols. Structurally diverse diaryl sulfides were prepared efficiently by using a catalyst system involving cheap and environment-friendly FeCl3 and non-toxic universal ligandl -proline. The reaction mechanism for the iron-catalyzed CS coupling reaction was investigated by means of density functional theory (DFT) methods on a model system. The calculations were performed using hybrid PBE1PBE functional in conjugation with the LANL-2DZ basis set. The key step involved in the mechanism is the formation of a reactant complex in which both reactants are electrostatically bound to Fe(III) proline complex catalyst. The elimination of HI occurs with a much lower TS energy (20.0 kcal/mol) than the uncatalyzed reaction (44.7 kcal/mol).